Effect of Controlled Hypotension on the Outcomes of Stapes Surgery - Andrade, António; Pinto, João Viana; Marques, Pedro; Leal, Manuel Mendes; Moura, Carla Pinto (International Archives of Otorhinolaryngology, 2025)
Stapes surgery (SS) benefits from adequate anesthetic bleeding control due to its microscopic nature and greater difficulty in hemostasis. Adequate hypotension during intervention is considered critical to achieving this goal.To evaluate the role of controlled hypotension (CH) on surgical outcomes in SS.We conducted a retrospective observational study in a tertiary academic center with adults submitted to SS from January 2017 to October 2022. Hypotension was considered controlled if the mean intraoperative arterial pressure was between 50 and 65 mmHg throughout the procedure. Patients were divided into CH and non-CH groups. Demographic data, medical history, anesthetic and surgical reports, perioperative complications, and audiometry results were studied.A total of 99 SS procedures were included. Of those, 23 met the criteria for CH. The non-CH group presented a nonsignificant longer operative time (71.4 ± 21.3 versus 83 ± 27.4 minutes; p = 0.065). No statistical difference was observed in complication rates related to the procedure (39.1 vs. 48.7%; p = 0.421). In terms of audiometric data, both groups showed comparable pre- and postoperative pure tone average (PTA) results (preoperative: 55.4 ± 11.3 versus 53.1 ± 16.2dB; p = 0.525; postoperative: 31.6 ± 10.2 versus 33 ± 17dB; p = 0.722). The postoperative average air-bone gap (ABG) was 9.3 ± 8.3 versus 10.1 ± 9dB; p = 0.709, while closure of the ABG was 24 ± 13.1 versus 19.7 ± 17dB; p = 0.287.Controlled hypotension in SS does not appear to impact the audiometric outcomes or complication rates, despite having a potential role in the surgery duration.
Keywords: otosclerosis; stapes surgery; controlled hypotension